SURFACE WATER MONITORING SYSTEM INSTALLED ON BOARD THE ICEBREAKER SHIRASE (Ninth Symposium on Polar Biology) - フクチ, ミツオ; ハットリ, ヒロシ; FUKUCHI, Mitsuo; HATTORI, Hiroshi (National Institute of Polar Research, 1987)
P(論文) A surface water monitoring system was designed and installed on board the icebreaker SHIRASE. The system consists of sensors unit, navigation information terminal and control unit. Water pumped up from an intake of hull (8 m depth) is led into the sensors unit so as to measure flow rate of water, water temperature, conductivity, dissolved oxygen, fluorescence intensity, size composition of plankton and concentration of nutrient salt. Analog signals from these sensors as well as digital data from navigation information terminal (GMT, position, ship's speed, sea depth, water and air temperature) are transferred into the control unit at intervals of every five minutes. All data are stored on a floppy disk mounted in the control unit simultaneously. A post data processing enables data editing, graphic displaying of time series data and geographical mapping. A field experiment in JARE-27 (1985/86) to the Antarctic Ocean revealed the usefulness of the present system for detecting fine-micro scale temporal and spatial variations of phytoplankton in relation to the oceanographic variables. departmental bulletin paper